The body of female victims of domestic violence - Machorrinho, Joana Palma; Veiga, Guida; Santos, Graça; Marmeleira, José (Cuestiones de Género: de la igualdad y la diferencia, 2019)
Domestic violence against women is a major reality in our present society, although our scares knowledge about all the process and, mostly, about the victims. It is quite a complex issue, because of its many characters, but also because there are a range of different theoretical perspectives for its comprehension. In this paper, we reviewed knowledge about phenomenology of the body, particularly the body of female victims of violence, taking in account the physical and psychic body, discussing the embodiment of violence and trauma. We try to understand how the body behaves in an aggressive situation, and how it compromises the battered woman behavior and health, or even how we can make from the body an empowerment resource.